Prevalensi penyakit pada ayam broiler di Kabupaten Serang, Provinsi Banten, Indonesia - Bahari, Akbar Satria; Armelia, Vony; Magfira (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2025)
Livestock farming plays a crucial role in providing food, raw materials, and essential services through animal breeding and management. This study aimed to provide an overview of the diseases affecting broiler chickens based on a case study from a commercial poultry company in Serang Regency, Banten Province, Indonesia. Data were collected from production cycles between 2021 and 2023, and disease identification was performed using a pathological diagnostic approach. The findings, presented descriptively in tabular form, indicated that broilers were affected by omphalitis, Newcastle disease, infectious bursal disease, chronic respiratory disease (CRD), colibacillosis, and aspergillosis. Colibacillosis was the most prevalent disease, with an incidence rate of 76%. These results highlight the importance of continuous disease monitoring and management to reduce mortality, maintain productivity, and ensure sustainability in the broiler industry